Povos indígenas na universidade: ação afirmativa e a geopolítica do conhecimento - Mattioli, Érica Aparecida Kawakami (Universidade Federal de São Carlos, 2014)
The selectivity concerning the access of indigenous students to Brazilian higher education have been due to the practices formed racially and the understanding of the political strategy of the education for the recognition of the otherness has appeased the definition of public policies of Affirmative Actions (AA) for groups historically considered subaltern. Affirmative action is often conceptualized as strategic mechanism when both racial tension and socio-economic inequality exist in order to counter the effects of a colonial history of discrimination and disadvantaging that has left huge silences and deformations in the historical narratives about indigenous people and their knowledge, philosophies, bodies and cultures. Therefore, we also can think about affirmative action in its epistemological dimension. A post-colonial reading of affirmative action policies in Brazilian universities focused on indigenous people provided the basis for our analysis. We argue that AA policies have a potential force to produce epistemological disruptions in university contexts. The goal of this research is both to analyze and to describe sociologically the experiences of indigenous students from different ethnic groups in the context of Affirmative Action Policies Program at Federal University of São Carlos. This study ends presenting discussions on how we can epistemologically rethink AA policies in Brazilian universities, especially regarding to indigenous people.
Keywords: Sociologia; Ações afirmativas; Povos indígenas; Ensino superior; Estudos pós-coloniais; Affirmative action; Indigenous people at universities; Postcolonial studies; Geopolitic of knowledge; CIENCIAS HUMANAS::SOCIOLOGIA